The Clinical, Radiologic, and Prognostic Differences Between Pediatric and Adult Patients With Myelin Oligodendrocyte Glycoprotein Antibody-Associated Encephalomyelitis - Xu, Jie; Liu, Lingjuan; Xiong, Jie; Zhang, Lu; Huang, Peng; Tang, Li; Xiao, Yangyang; Li, Xingfang; Li, Jian; Luo, Yingying; Li, Huiling; Mao, Dingan; et al. (Frontiers in Neurology, 2021)
Purpose: To evaluate the clinical differences between pediatric and adult patients with myelin oligodendrocyte glycoprotein antibody-associated encephalomyelitis (MOG-EM). Methods: We retrospectively reviewed the clinical features of pediatric and adult patients with MOG-EM in our center between November 2015 and October 2020. Results: Twenty-eight pediatric patients and 25 adults were admitted to our study. Bilateral optic neuritis (BON) was the most common initial phenotype in the pediatric group but less common in the adult group (28.57% vs. 0%, p=0.0119). Almost half of the adult patients presented with neuromyelitis optica spectrum disease (NMOSD), which was less prevalent among the pediatrics (48% vs. 21.43%, p=0.0414). Visual impairment was the most common symptom in both groups during the initial attack (pediatric group, 39.29%; adult group, 64%) and throughout the full course (pediatric group, 57.14%; adult group, 72%). More pediatric patients suffered from fever than adult patients at onset (pediatric group, 28.57%; adult group, 4%; p=0.0442) and throughout the full course (pediatric group, 39.29%; adult group, 12%; p=0.0245). Multiple patchy lesions in subcortical white matter (42.55%), periventricular (29.79%), infratentorial (23.40%) and deep gray matter (23.40%) were frequent in all cases, no significant difference was found between the two groups, while bilateral optic nerve involvement was more frequent in pediatric group (61.54% vs 14.29%, p=0.0042) and unilateral optic nerve involvement was higher in adult group (64.29% vs 15.38%, p=0.0052). At the last follow-up, adult patients had a higher average EDSS score (median 1.0, range 0-3) than pediatrics (median 0.0, range 0-3), though not significant (p=0.0752). Patients aged 0-9 years (61.54%) and 10-18 years (70%), and patients presenting with encephalitis/meningoencephalitis (100%) and ADEM (75%) were more likely to recover fully. Conclusions: Visual impairment was the dominant symptom in both pediatric and adult patients, while fever was more frequent in pediatric patients. Data suggested that BON and bilateral optic nerve involvement were more common in pediatric cases whereas NMOSD and unilateral optic nerve involvement were more prevalent in adults. The younger patients and patients presenting with encephalitis/meningoencephalitis and ADEM tended to recover better.